Context and Implications Document for: Meta‐synthesis and comparative meta‐analysis of education research findings: some risks and benefits. Issue 1 (February 2016) - Higgins, Steve
Abstract : This guide accompanies the following article: Steve Higgins, Meta‐synthesis and comparative meta‐analysis of education research findings: some risks and benefits, Review of Education, DOI:10.1002/rev3.3067